More on phi-features in and out of copular sentences: A reply to Béjar & Kahnemuyipour 2018 - HARTMANN, JUTTA M.; HEYCOCK, CAROLINE (Journal of linguistics, 2018)
Jutta M. Hartmann and Caroline Heycock continue their discussion with Susana Béjar and Arsalan Kahnemuyipour (same journal issue) based on Béjar and Arsalan's original article "Non-canonical agreement in copular sentences" (Journal of Linguistics, 53.3, 463–499).